Subinhibitory Antimicrobial Concentrations: A Review of In Vitro and In Vivo Data - George G Zhanel; Daryl J Hoban; Godfrey KM Harding (Canadian Journal of Infectious Diseases)
Antimicrobial activity is not an ‘all or none’ effect. An increase in the rate and extent of antimicrobial action is usually observed over a wide range of antimicrobial concentrations. Subinhibitory antimicrobial concentrations are well known to produce significant antibacterial effects, and various antimicrobials at subinhibitory concentrations have been reported to inhibit the rate of bacterial growth. Bacterial virulence may be increased or decreased by subinhibitory antimicrobial concentrations by changes in the ability of bacteria to adhere to epithelial cells or by alterations in bacterial susceptibility to host immune defences. Animal studies performed in rats, hamsters and rabbits demonstrate decreased bacterial adherence, reduced infectivity and increased survival of animals treated with subinhibitory antimicrobial concentrations compared to untreated controls. The major future role of investigation of subinhibitory antimicrobial concentrations will be to define more fully, at a molecular level, how antimicrobials exert their antibacterial effects.